(untitled) - Plummer, Charles C. (Boston, 2005)
"Physical Geology, 10/e" is the latest refinement of a classic introductory text that has helped countless students learn basic physical geology concepts for over 20 years. Students taking introductory physical geology to fulfill a science elective as well as those contemplating a career in geology will appreciate the accessible writing style and depth of coverage in "Physical Geology, 10/e". Hundreds of carefully rendered illustrations and accompanying photographs correlate perfectly with the chapter descriptions to help the reader quickly grasp new geologic concepts. Numerous chapter learning tools and a rich Online Learning Center website further assist students in their study of physical geology. For professors, McGraw-Hill offers a complete supplement package consisting of slides, transparencies, computerized testbank, PowerPoint lectures, and digital images of every single piece of artwork and photograph in the text. These valuable supplements will make teaching easier and assist in fully conveying important concepts to students. McGraw-Hill is committed to adding considerable quality to each new edition of "Physical Geology" in the form of new and revised content, artwork, supplements, and media technology. Professors can adopt "Physical Geology, 10/e" with confidence and count on the authors and McGraw-Hill to help them most effectively teach introductory physical geology to their students.
Keywords: Vật lý địa chất,Physical geology